Effectiveness of Kirinyuh Weed LOF , AMF and Local Corn Production on Marginal Land in Southeast Sulawesi - Nurmas, Andi; Adawiyah, Robiatul; Hasid, Rachmawati (Asosiasi Mikoriza Indonesia, 2024)
This research aims to determine the effectiveness of kirinyuh weed LOFand AMF on local corn production on marginal land in Southeast Sulawesi. Research was carried out in the Experimental Garden Field Lab II and Lab. Agronomy Unit, Faculty of Agriculture, UHO, Kendari, from May-October 2022. The research used a Randomized Block Design (RBD) with a factorial pattern consisting of two factors. The first factor is liquid organic fertilizer (LOF) which consists of 4 levels, namely without LOF (P0), LOF 20 mL L-1 water (P1), LOF25 mL L-1 water (P2), LOF 30 mL L-1 water (P3 ). The second factor is FMA which consists of 3 levels, namely without AMF (M0), FMA 15 g/ planting hole (M1), and FMA 20 g/planting hole (M2). The variables observed were plant height, number of leaves, stem diameter, ear length, number of rows per ear, ear diameter, weight of 100 seeds and productivity. The research results showed that there was no interaction effect of LOF and AMF treatment on plant height and productivity but had a significant effect on the number of leaves, stem diameter, ear length, number of rows per ear, weight of 100 seeds and productivity. The LOF treatment of LOF 30 mL L-1 water and AMF 15 g/plant is the best treatment for local corn production on marginal land.